Genomic exploration of retrocopies in Insect pests of plants and their role in the expansion of heat shock proteins superfamily as evolutionary targets - Aftab Ahmad; Wenyu Zhang (BMC Genomics)
Abstract Background Gene duplication is a dominant mechanism for the evolution of genomes and plays a key role in genome expansion. Gene duplication via retroposition produces RNA-mediated intron-less copies called retrocopies, that may gain regulatory sequence and biological function to generate retrogenes. Retrocopies dynamics have been reported in several model insect species, but there is still a huge knowledge gap about retrocopies dynamics in most insects, and their role in adaptation. Results In this study, we reported retrocopy dynamics in 40 species of insect pests of plants belonging to six insect orders. We identified a total of 9,930 retrocopies, which is so far the largest set of retrocopies identified in insects. The identified retrocopies were further grouped into 2,599 Retrogenes, 4,578 Chimeras, 1,241 Intact retrocopies, and 1,512 Pseudogene. We also analyzed all the identified retrogenes that were annotated into 506 gene families. The highest number of retrogenes annotated belong to the heat shock proteins superfamily and are present across all the 40 species from the six orders. We found a significant expansion of the heat shock protein superfamily in the studied species. Almost all the retrogenes, including those belonging to heat shock proteins, are under purifying selection. In summary, we report the retrocopies and retrogenes dynamics in a large set of insect pests of plants and the expansion of the heat shock protein family due to retroposition. Conclusion This study unveils retrocopy dynamics in the insect pests of plants and highlights the evolution of new genes due to retroposition, and their role in important gene families’ expansion.